Our Children Are Not Alone - ISAR Productions
Filmed in Kenya and Rwanda, this is an awareness film to help churches understand who are orphans and vulnerable children, and what are their needs. At eight minutes run time this is a good film to choose as an introduction to a discussion, or as an awareness message in a worship service. Much of its power comes from the refrain of Scripture texts that punctuate the questions raised. It is a golden award winning film. Translations are: English, Kiswahili, Kinyarwanda, Kirundi, Malagasi. It was originally produced under ISAR productions. NTSC, PAL
Paid